2022
DOI: 10.2147/jir.s348539
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Complement C1q and C3 Level with Age-Related Macular Degeneration in Women

Ma Y1,
et al.

Abstract: Purpose To investigate the association between serum complement components and age-related macular degeneration (AMD). Patients and Methods A total of 118 AMD patients and age- and sex-matched 106 control subjects were included. Demographic data and the level of serum complement component (C)1q, C3 and C4 were evaluated. Based on sex, the subjects were stratified into male and female subgroups. Results The level of C1q (226.31±45.33mg/dL) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…When MBL recognizes and binds to mannose residues on the pathogen surface, activated MASPs can subsequently initiate the complement cascade through cleavage of complement proteins C2 and C4 to generate C3 and C5 convertases ( 6 , 7 ). Indeed, overactivation of the complement system produces excessive inflammatory responses, resulting in β-cell function impairment and insulin resistance and thus glucose dyshomeostasis via activating the production of inflammatory mediators and stimulating macrophage infiltration ( 8 , 9 ). In recent years, several studies have reported that increased MASPs were associated with an elevated risk of prediabetes and type 2 diabetes ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…When MBL recognizes and binds to mannose residues on the pathogen surface, activated MASPs can subsequently initiate the complement cascade through cleavage of complement proteins C2 and C4 to generate C3 and C5 convertases ( 6 , 7 ). Indeed, overactivation of the complement system produces excessive inflammatory responses, resulting in β-cell function impairment and insulin resistance and thus glucose dyshomeostasis via activating the production of inflammatory mediators and stimulating macrophage infiltration ( 8 , 9 ). In recent years, several studies have reported that increased MASPs were associated with an elevated risk of prediabetes and type 2 diabetes ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%